Pengaruh Job Insecurity, Job Stress, Work-Family Conflict Terhadap Turnover Intention Pada Karyawan BPO di Yogyakarta Dimediasi Job Satisfaction - M. Nur Faqih; Achmad Sobirin (Journal Economic Insights, 2024)
This study aims to examine and analyze the influence of job insecurity, job stress and work-family conflict on turnover intention which is mediated by job satisfaction. This research is quantitative in nature, the data collection tool uses a questionnaire with a sample of 221 employees who work at BPO companies in Yogyakarta and uses the PLS (Partial Least Square) analysis tool. The results of this study indicate that job insecurity has a significant effect on job satisfaction, job stress has no effect on job satisfaction, work-family conflict has an effect on job satisfaction, job satisfaction has an effect on turnover intention, job insecurity has a positive effect on turnover intention, job stress has no influence on turnover intention, work-family conflict has a positive effect on turnover intention, job satisfaction mediates the relationship between job insecurity and turnover intention, job satisfaction does not mediate the relationship between job stress and turnover intention, job satisfaction mediates the relationship between work family conflict and turnover intention..